EXPRESSION OF ANTIVIRAL GENE ON TIGER SHRIMP Penaeus monodon AT DIFFERENT TISSUE AND BODY SIZE - Andi Parenrengi; Andi Tenriulo; Samuel Lante (Indonesian Aquaculture Journal, 2012)
The role of tiger shrimp defense against invading pathogen on molecular level such antiviral gene expression is limited to be reported. Gene expression is a process which codes information of genes that is converted to the protein as a phenotype. Distribution of PmAV antivirus gene, that has been reported as an important gene on non-specific response immune, is needed to be observed to several organs/tissues and size of tiger shrimp. The aim of this study is to determine the distribution of gene antiviral expression at several organ/tissue and size of shrimp. The organs/tissues observed in this study were: gill, hepatopancres, muscle tissue, eyes, heart, stomach, gonad, and intestine. While the size of shrimp consisted of three groups, those are: (A) 10-20 g/ind., (B) 30-40 g/ind., and (C) 60-70 g/ind. Analysis of antiviral gene expression was performed by RNA extraction, followed by the cDNA syntesis, and amplification of gene expression by semi-quantitative PCR. The result of PCR optimation showed the optimal concentration of cDNA and primer was 1 μL and 50 mol, respectively for PCR final volume of 25 μL. Antiviral gene was expressed on the hepatopancreas and stomach in percentage of 50.0% and 16.7%, respectively. While the highest percentage of individual expressing the antiviral gene was observed in the shrimp size of C (66.7%), followed by B (50.0%) and A (16.7%). The result of study implied that the hepatopancreas has importantly involed in tiger shrimp defense mechanism on viral infection.